2017
DOI: 10.18512/1980-6477/rbms.v16n2p287-296
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Selection for Drought Tolerance in Maize Through Agronomic Traits and Seeds

Abstract: -High prolificacy, stay green, and a reduced anthesis-silking interval are among the traits most used for indirect selection for drought tolerance. The objective of this research was to evaluate five maize lines from the maize breeding program of the company Geneseeds Recursos Genéticos Ltda, to drought tolerance, grown at four plant population sizes, 40, 60, 80 and 100 thousand plants ha -1 . In these conditions, the following traits were evaluated: prolificacy, stay green and interval between female and male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Subsequently, the seeds were stored in a cold room at 10 °C. These seeds (from both lines and from F 1 and reciprocal hybrids) were obtained by Abreu et al (2017) and used in this study.…”
Section: Line 57 and 91 Phenotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the seeds were stored in a cold room at 10 °C. These seeds (from both lines and from F 1 and reciprocal hybrids) were obtained by Abreu et al (2017) and used in this study.…”
Section: Line 57 and 91 Phenotypingmentioning
confidence: 99%
“…Considering this, the germination under stress simulation in laboratory may be a faster alternative. This can be observed based on the studies of Abreu et al (2017;, which used germination tests in laboratory as indirect methods to phenotype maize lines. Marques et al (2019;2020) also studied seed, seedling, and reserve tissue gene expression under stress conditions, with significant differences among genotypes regarding the response to water deficit.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the transcript expressions, the 91-T line had greater expression of the ZmLEA3, ZmAN13, ZmCPK11 and ZmPP2C genes was observed in seeds. Abreu et al (2017) also evaluated this line and considered it promising for drought tolerance by evaluations of grain yield, prolificacy, and intervals between female and male flowering. When evaluating genotypes with different levels of tolerance at high temperatures, Dutra et al (2015) concluded that the 91-T line is more tolerant in high-temperature conditions.…”
Section: Transcript Analysismentioning
confidence: 99%
“…Over 90% of the maize area grown worldwide is non-irrigated, and annual yield losses resulting from drought are estimated at approximately 15% of total yield potential. Losses are significant in tropical countries that rely on a relatively unpredictable rainy season for crop growth (ABREU et al, 2017). The study conducted by ADEBAYO et al (2014) reported that water stress leads to lower grain yield, and losses can be as high as 80% during the flowering and grain-filling stages.…”
Section: Introductionmentioning
confidence: 99%